Power Lines: Unobtrusive Assessment of E-mail Subject Line Impact on Organization Website Use. Issue 3 (3rd July 2019) - Calfano, Brian
Abstract : Scholars have generally found e-mail–based effects to be limited, despite suggestions from marketing consultants that techniques such as message personalization and emotion-based content make e-mail campaigns more successful. Key in e-mail personalization is the subject line. To my knowledge, however, no one has examined the direct effects of e-mail subject lines using a field experiment with unobtrusive behavioral measures (i.e., tracking e-mail open rates). To address this gap, I leverage a field experiment using 82, 000 e-mail addresses from a state-based Planned Parenthood contact list to determine whether randomly assigned subject line content impacts e-mail open rates. My results show that subject line personalization has a limited effect on open rates, but that personalization—when combined with subject line reference to emotion—may affect downstream behavior among a small percentage of e-mail recipients.